Contributions of local soap enterprise to livelihood of rural women in selected local government areas of Oyo State (2012)
The rural women engage in diverse livelihood activities to provide for their immediate, family needs. This study examined the contributions of local soap enterprise to the livelihood of rural women in Oyo state. A purposive sampling technique was used to select two local government areas from which two communities each were selected. Snowball technique was used to generate list of women involved in the production and marketing of local soap. Thirty respondents were randomly selected from the list generated in each community to give total sample size of 120 respondents. Data collection was done through the use of interview schedule and analysed using both descriptive and inferential statistics (Chi-square). Results reveal that most of the respondents (62.4%) were in their active ages. 77.5% had formal education, and 71.9% belonged to an association. About 54.0% produced local soap on weekly basis and 98.2% produced far the purpose of generating income. Greater percentage (59.0%) used calabash as a unit of measurement while 43.0% were both processors and marketers of local soap. A Iso. 61.4% made use of family labour and 77.2% had high perception towards local soap enterprise's contribution to livelihood due to the high income generated from it. Level of education had significant relationship (x(2) = 12.885, p-value =0.024) with contribution of local soap enterprise. Thus, the study concludes that local soap enterprise is an important contributor to livelihood in the study area. Hence, the activity should be given adequate attention in terms of provision of loans and promotion of local market for improved productivity and overall standard of living of the entrepreneurs.